2018
DOI: 10.3892/ol.2018.9009
|View full text |Cite
|
Sign up to set email alerts
|

Scinderin‑knockdown inhibits proliferation and promotes apoptosis in human breast carcinoma cells

Abstract: Previous studies have reported that scinderin (SCIN) affects multiple cellular processes, including proliferation, migration and differentiation in cancer. However, the specific role of SCIN in breast cancer (BC) cells is unknown. Immunohistochemistry was used to investigate SCIN expression in 46 BC and 21 mammary fibroadenoma or fibroadenomatoid hyperplasia tissue samples. SCIN expression was ablated in MDA-MB-231 and T-47D cells using lentivirus-mediated small interfering RNA technology. Cell proliferation w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 32 publications
0
6
0
Order By: Relevance
“…Further, the in vitro experiment demonstrated that RSRC2 could inhibit the MDA-MB-231 cells and MDA-MB-453 cells clonogenic ability, adhesion, migration and invasion ability. The transcriptome array data analysis identified differentially expressed genes in the MDA-MB-231 shRSRC2 cells and control cells and identified SCIN, IL6, CXCL8, CXCL1, PTGS2, IL1B, NOS3, ICAM1, moesin and DCAF6, which were reported to be involved in cell proliferation, migration and cell adhesion [ 15 , 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 ]. The intersection set analysis of the bioinformatics database and transcriptome array data identified six common genes, FSTL1, GDF15, IQSEC2, KDM3A, LTC4S and TCTEX1D4, in which most of them were involved in tumor cell proliferation and growth [ 29 , 30 , 31 , 32 , 33 , 34 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Further, the in vitro experiment demonstrated that RSRC2 could inhibit the MDA-MB-231 cells and MDA-MB-453 cells clonogenic ability, adhesion, migration and invasion ability. The transcriptome array data analysis identified differentially expressed genes in the MDA-MB-231 shRSRC2 cells and control cells and identified SCIN, IL6, CXCL8, CXCL1, PTGS2, IL1B, NOS3, ICAM1, moesin and DCAF6, which were reported to be involved in cell proliferation, migration and cell adhesion [ 15 , 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 ]. The intersection set analysis of the bioinformatics database and transcriptome array data identified six common genes, FSTL1, GDF15, IQSEC2, KDM3A, LTC4S and TCTEX1D4, in which most of them were involved in tumor cell proliferation and growth [ 29 , 30 , 31 , 32 , 33 , 34 ].…”
Section: Discussionmentioning
confidence: 99%
“…The effect of SCIN on cancers was controversial among different investigators. There is a study [ 15 ] that demonstrates that SCIN knockdown inhibits breast cancer cell proliferation and induces apoptosis. However, the functional contribution of SCIN expression in TNBC progression has been relatively under-reported.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Another study found SCIN was highly expressed in prostate cancer and promoted prostate cancer cell proliferation by the EGFR and MEK/ERK singling pathway [ 6 , 24 ]. Furthermore, SCIN was increased in breast cancer and the knockdown of SCIN could inhibit breast cancer cell proliferation and induce apoptosis [ 25 ]. However, in other research projects, the SCIN expression was low and associated with poor progress in acute myeloid leukemia, hepatocellular carcinoma, and gastric cancer [ 8 , 26 , 27 ].…”
Section: Discussionmentioning
confidence: 99%
“…It was recently shown that cell surface expression of both PD-L1 and PD-L2 were increased in IPF fibroblasts compared to healthy controls [72], and the inhibition of Pd-l1 significantly reduced lung fibrosis in bleomycin-mice models [73]. SCIN is involved in cytoskeletal remodeling and the silencing of SCIN in cancer cells inhibits cell proliferation [74][75][76]. SMARCA4 is part of the chromatin remodeling complex SWI/SNF.…”
Section: Discussionmentioning
confidence: 99%